Development of an Archival Management Application for Integration and Monitoring of Documents in Coordination Meetings - Syarof, Siti Minatus; Ulum, Muhamad Bahrul (Sebatik, 2024)
Archival management is of significant importance in institutions, requiring proper maintenance and organization of activity records. The Coordinating Ministry for Economic Affairs (Kemenko Perekonomian), as a government body, is responsible for coordination, synchronization, and control in the economic sector. Its coordination activities include inter-ministerial meetings aimed at formulating strategic policies and actions in the economic field. The Secretariat Division is tasked with facilitating these coordination meetings. The coordination meeting process involves preparing several key components, such as meeting invitations, materials, and documentation, including participant lists, recordings, minutes, and transcripts. Currently, the archiving of meeting documents is fragmented across various sub-sections within the Secretariat Division, leading to inefficiencies in document management. Furthermore, the absence of a centralized system to accommodate all coordination meeting records makes document monitoring challenging. To address these issues, an application has been designed to store meeting documents in a unified database, enabling more efficient document management, integration, and monitoring. The development of this application utilizes the waterfall model with UML diagram modeling. This application is expected to enhance document management processes within the Secretariat Division and provide greater convenience for users.